Effect of Vitamin C and Selenium on Some Physiological and Reproductive Characters in Adult Roosters Exposed to Oxidative Stress Induced by Hydrogen Peroxide: MSMS AL-Ma’atheedi and A.A. Hassan - المعاضيدي محمودسالم محمدشيت (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was designed to investigate the effect of Vitamin C (450 mg/kg diet) and sodium selenite (0.5 mg/kg diet) in adult white Leghorn male chickens (30 weeks of age), whose concomitantly exposed to oxidative stress induced by hydrogen peroxide (0.5%) supplemented with drinking water for 6 weeks on reproductive performance. Semen were collected at 0, 2, 4 and 6weeks, The study results showed that hydrogen peroxide treatment caused a significant decrease in the body weight, sperm concentration, mass motility and individual motility during experimental period. Also a decrease in testosterone and testis glutathione concentration at the 6th week of the treatment, accompanied with a significant increase in dead and abnormal sperm percentage, testis malondialdehyde level compared with the control group. Histopathological changes revealed presence of necrosis and sloughing in the epithelial lining of the semineferous tubules and vacuolar degeneration of the supporting cells that fall in the lumen of the semineferous tubules and necrosis of interstitial cells. Vitamin C and sodium selenite with hydrogen peroxide caused a significant increase in body weight, sperm concentration, mass motility and individual motility during the experimental period, testosterone and glutathione level, accompanied with a significant decrease in dead and abnormal sperm percentages and Malondialdehyde level compared with hydrogen peroxide. In addition to the improvement in the histological picture of the semineferous tubules, mitosis germ cells were observed through their arrangement in circular tubules. It was concluded from this study that Vitamin C and Sodium selenite reverse the adverse effects produced by hydrogen peroxide on certain physiological and reproductive aspects in adult male chickens.